Non-invasive facial enhancement through facial muscle gymnastics (Journal of Face Aesthetics, 2024)
The human face is shaped by as many as 70 muscles, which are activated during the day. The visual assessment of the face changes with age, which is associated with the constant passage of time. The process of facial aging is complex, including changes in the skin, connective tissue and muscles. Regular exercises have a positive effect on both the strength of the facial muscles and their rejuvenating effects. Rejuvenating the face, as well as activating the facial expression muscles, can help you look younger, happier and more joyful. Youthful facial contours should be taken care of from adolescence by performing simple exercises. Facial gymnastics is a must at any age, for both women and men, also in cases of using aesthetic medicine procedures.
Keywords: facial muscle gymnastics; non‑invasive aesthetic medicine; facial yoga; slowing down facial ageing